Palliative Care in the Delivery Room: Challenges and Recommendations - Lars Garten; Kerstin von der Hude (MDPI AG, 2022)
Palliative care in the delivery room is an interprofessional and interdisciplinary challenge addressing the dying newborn and parents as well as the caregivers. It differs in some significant aspects from palliative care in the neonatal intensive care unit. Clinical experience suggests that many details regarding this unique specialized palliative care environment are not well known, which may result in some degree of insecurity and emotional distress for health care providers. This article presents basic background information regarding the provision of palliative care to newborns within the delivery room. It offers orientation along with a preliminary set of practical recommendations regarding the following central issues: (i) the basic elements of perinatal palliative care, (ii) the range of non-pharmacological and pharmacological interventions available for infant symptom control near the end of life, (iii) meeting the personal psychological, emotional, and spiritual needs of the parents, and (iv) care and self-care for medical personnel.